HARNESSING DIGITAL FINANCIAL INNOVATION FOR SUSTAINABLE BANKING AND INCLUSIVE ECONOMIC GROWTH IN UZBEKISTAN (Innovate Conferences, 2025)
This study investigates the strategic integration of digital financial technologies in Uzbekistan's banking sector, emphasizing their role in enhancing financial inclusion and fostering sustainable development. The paper analyzes current trends, regulatory initiatives, and the socio-economic impacts of FinTech adoption. It highlights how innovative financial services reduce inequality, enhance resource efficiency, and contribute to environmental sustainability. The paper also identifies critical barriers and provides actionable policy recommendations for building a resilient digital financial ecosystem tailored to Uzbekistan's developmental priorities.